Interplay of point and planar defects in the phase state formation and dynamics of Abrikosov vortices in YBa₂Cu₃O₇-δ crystals - Petrusenko, Yu.T.; Bondarenko, A.V. (Functional Materials, 2009)
The rotation of magnetic field H off the plane of twin boundaries (TBs) has been found to induce transition of an ordered vortex solid phase to a disordered one due to transverse deformations of vortex lines near the TBs. It has been shown that the variation of both the depinning current density Jc and the activation energy Uplef corresponding to plastic vortex creep with angle θ = ∠ H,TB are not changed qualitatively with increasing concentration of point defects nd, but this variation is strongly affected by the evolution of a kinked structure of vortex lines with the angle θ. It has been also shown that the current density Jc and energy Uplef behave quite differently as the angle θ and the concentration nd vary, and in particular, angular variation of the pinning force in the creep regime Fp, which is defined by competition between the current density Jc and the energy Uplef, depends on the concentration nd and on the driving force value. Встановлено, що поворот магнітного поля Н з виходом з площини меж двійників (МД) ініціює перехід упорядкованої вихрової фази у неупорядковану внаслідок появи поперечних деформацій вихрових ниток в околі МД. Показано, що зміна густини струму депінінгу Je та енергії активації Uplef, яка відповідає пластичному крипу вихорів, з кутом θ = ∠Н,МД якісно не змінюється при збільшенні концентрації точкових дефектів nd, і ця зміна визначається еволюцією зигзагоподібної структури вихрових ниток з кутом θ. Густина струму Je та енергія Uplef змінюються у протилежних напрямках як з кутом θ, так і з концентрацією nd, а конкретна кутова залежність сили пінінгу у режимі крипу FP, яка визначається конкуренцією між густиною струму Je та енергією Uplef, залежить від концентрації nd та від величини рушійної сили. Установлено, что поворот магнитного поля Н с выходом из плоскости границ двойников (ГД) инициирует переход упорядоченной вихревой фазы в неупорядоченную из-за появления поперечных деформаций вихревых нитей в окрестности ГД. Показано, что изменение плотности тока депиннинга Je и энергии активации Uplef, соответствующей пластическому крипу вихрей, с углом θ = ∠Н,ГД качественно не меняется при увеличении концентрации точечных дефектов nd, и это изменение определяется эволюцией зигзагообразной структуры вихревых нитей с углом θ. Плотность тока Je и энергия Uplef изменяются противоположным образом как с углом θ, так и с концентрацией nd, а конкретная угловая зависимость силы пиннинга в режиме крипа FP, которая определяется конкуренцией между плотностью тока J е и энергией Uplef, зависит от концентрации nd и величины движущей силы.